2018
DOI: 10.1371/journal.pone.0204265
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Proximity Sequencing (Pro-Seq): A method to improve DNA sequencing accuracy without the cost of molecular barcoding redundancy

Abstract: A challenge in the clinical adoption of cell-free DNA (cfDNA) liquid biopsies for cancer care is their high cost compared to potential reimbursement. The most common approach used in liquid biopsies to achieve high specificity detection of circulating tumor DNA (ctDNA) among a large background of normal cfDNA is to attach molecular barcodes to each DNA template, amplify it, and then sequence it many times to reach a low-error consensus. In applications where the highest possible specificity is required, error … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Hence, other methods providing high performance for detecting low frequency mutations are needed to be applied. Many error correction methods on WES have been developed and commonly used nowadays [27][28][29][30][31][32][33] , the unique molecular identifiers (UMIs) based error correction strategy is very useful in the above context. UMIs can tag sequences to help track molecules and remove errors in amplification and sequencing [34][35][36][37][38] , Michael et al developed a method called "duplex sequencing" which tagged the sequencing adapter by a degenerated 12 randomized base (Duplex Tag) and 4 base length fixed sequence 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, other methods providing high performance for detecting low frequency mutations are needed to be applied. Many error correction methods on WES have been developed and commonly used nowadays [27][28][29][30][31][32][33] , the unique molecular identifiers (UMIs) based error correction strategy is very useful in the above context. UMIs can tag sequences to help track molecules and remove errors in amplification and sequencing [34][35][36][37][38] , Michael et al developed a method called "duplex sequencing" which tagged the sequencing adapter by a degenerated 12 randomized base (Duplex Tag) and 4 base length fixed sequence 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, duplex proximity sequencing physically links copies of every template DNA strand so that both the duplex strands are sequenced as a single cluster during sequencing, and the mutant detected in the cluster can be traced back to both DNA strands (þ and À) without the need for duplex sequencing with UIDs. 62 Similarly, in another UID-free method, post-NGS sequencing, the reads that have low-level mutations are physically and selectively isolated and amplified and the sequence is confirmed by either NGS or Sanger sequencing, thus avoiding the need to sequence the wild-type sequence background. 63 Furthermore, a recent study has demonstrated the use of technical replicates from the level of library preparation as a solution to accurately detect low-level mutations without using UID tagging.…”
Section: Non-uid Approachesmentioning
confidence: 99%
“…Modern NGS systems produce errors at a per-base rate of 10 −2 to 10 −3 , but clinically relevant mutations have been revealed to be at, or below, that level making many true variants undetectable. 47 In recent years error correction strategies have been developed and today NGS and liquid biopsy have a great potential in a gene’s mutational status detection and impact positively on diagnostics and cancer management. Recently, ctDNA liquid biopsies have been adopted for several personalized medicine applications, including guiding treatment selection during monitoring, minimum residual disease detection, and even screening (ClinicalTrials.gov NCT02808884; NCT02889978).…”
Section: Discussionmentioning
confidence: 99%